“Las actividades plásticas en el desarrollo de la psicomotricidad de los estudiantes del tercer año de la Unidad Educativa “Milton Reyes”, período 2017-2018” - López Pinduisaca, Estefanía Maricela (2018)
The present research titled “The plastic activities in the development of the psychomotricity in the students of Third Year of the Unidad Educativa "Milton Reyes" This research has the purpose analyzing the theoretical framework of the psychomotricity and plastic activities that is used as scientific bases for the development of appropriate methodological strategies and in this way contribute to the proper development of motor skills, as well as propose plastic activities that help the formation of motor skills, which are expressive and creative. The methodology applied is of qualitative design, whose characteristics will be the basis for statistical analysis. The type of research correspond to a field process because it was carried out in the aforementioned institution. The method applied is bibliographic and nonexperimental, for this study a population of 26 boys and girls were selected, the data was obtained through for the observation sheet, which it was possible to conclude that 58% are in the process of developing their psychomotricity, 35% have an acquired learning and do not psychomotricity developed. For this, it is concluded to propose the application of plastic activities that help the development of both thin and thick psychomotor skills in students and in this way develop motor skills, expressive and creative.